Evaluating Efficiencies of Dual AAV Approaches for Retinal Targeting - Carvalho, Livia S.; Turunen, Heikki T.; Wassmer, Sarah J.; Luna-Velez, María V.; Xiao, Ru; Bennett, Jean; Vandenberghe, Luk H. (Frontiers in Neuroscience, 2017)
Retinal gene therapy has come a long way in the last few decades and the development and improvement of new gene delivery technologies has been exponential. The recent promising results from the first clinical trials for inherited retinal degeneration due to mutations in RPE65 have provided a major breakthrough in the field and have helped cement the use of recombinant adeno-associated viruses (AAV) as the major tool for retinal gene supplementation. One of the key problems of AAV however, is its limited capacity for packaging genomic information to a maximum of around 4.8 kb. Previous studies have demonstrated that homologous recombination and/or inverted terminal repeat (ITR) mediated concatemerization of two overlapping AAV vectors can partially overcome the size limitation and help deliver larger transgenes. The aim of this study was to investigate and compare the use of different AAV dual-vector approaches in the mouse retina using a systematic approach comparing efficiencies in vitro and in vivo using a unique oversized reporter construct. We show that the hybrid approach relying on vector genome concatemerization by highly recombinogenic sequences and ITRs sequence overlap offers the best levels of reconstitution both in vitro and in vivo compared to trans-splicing and overlap strategies. Our data also demonstrate that dose and vector serotype do not affect reconstitution efficiency but a discrepancy between mRNA and protein expression data suggests a bottleneck affecting translation.